Invertebrate systematics or spineless taxonomy?* - Wheeler, Quentin D. (Zootaxa, 2007)
What progress has been made since these words were written by Wilson more than twenty years ago?  The answer is a mixed one.  We have so far to go in our inventory of Earth’s species that it is easy to be discouraged by advances measured in hundreds of thousands of new species rather than millions.  Yet there has been progress and the potential exists for rapid advances.  Excellent work continues to be done as evidenced by this special issue of ZooTaxa and the burgeoning popularity of this e-journal. Innovative new funding has appeared at the U. S. National Science Foundation including the Partnerships to Enhance Expertise in Taxonomy (PEET), Assembling the Tree of Life (AToL), and particularly encouraging, the Revisionary Syntheses in Systematics (RevSys) and Planetary Biodiversity Inventory (PBI) projects that focus specifically on descriptive taxonomy.  Most promising is an emerging new field, cybertaxonomy, that represents the convergence of traditional taxonomic goals with new, equally ambitious ones, fueled by the full potential of cyberinfrastructure, digital technology, information science, and computer engineering (Atkins et al. 2003, Page et al. 2005, Wheeler 2004, Wheeler et al. 2004).